Answer:
Therefore ,
![y= (Ae^(kt))/(1+Ae^(kt) )](https://img.qammunity.org/2021/formulas/mathematics/college/h7h0xl0w8q3o10y8xiudic01hxg2w3an3f.png)
Explanation:
The fraction of population who have heard rumor = y
The fraction of population who haven't heard rumor = 1-y
The rate of of spread (y'(t)) is proportional to the product of the fraction of population who have heard rumor the fraction of population who have heard rumor.
Therefore
y'(t) ∝ y (1-y)
⇒ y'(t) =k y (1-y) [ k = constant of proportional]
![\Rightarrow (dy)/(dt)=ky(1-y)](https://img.qammunity.org/2021/formulas/mathematics/college/3110myvffzwq3nqosxnyz4vt7qj2g5m8ri.png)
![\Rightarrow (dy)/(y(1-y))=k \ dt](https://img.qammunity.org/2021/formulas/mathematics/college/y4imb8vwqqfv7no3z7cr9p9jp00uh3cwv8.png)
Integrating both sides
![\Rightarrow \int(dy)/(y(1-y))=\int k \ dt](https://img.qammunity.org/2021/formulas/mathematics/college/42uatayctcboam7ccbdcnq8q471j40jnv4.png)
![[\because (1)/(y(1-y)=(1)/(y)+(1)/(1-y) ]](https://img.qammunity.org/2021/formulas/mathematics/college/5yo9rd8iw0t4gnlnhsu24dd2y10m695zs5.png)
[ c = arbitrary constant]
![\Rightarrow ln|(y)/(1-y)|=kt +c](https://img.qammunity.org/2021/formulas/mathematics/college/i4d1sufgrf1a50ccqvtu6k4lc6oop91oc9.png)
![\Rightarrow (y)/(1-y)= e^(kt+c)](https://img.qammunity.org/2021/formulas/mathematics/college/wfqv8ib6lywo7cge7s1hqosbz6lspp27za.png)
[ Here
]
![\Rightarrow y = Ae^(kt)(1-y)](https://img.qammunity.org/2021/formulas/mathematics/college/3qrpz9s41x6drfxauy6wyotkngh43gs93q.png)
![\Rightarrow y = Ae^(kt)-y Ae^(kt)](https://img.qammunity.org/2021/formulas/mathematics/college/lqlv7b37b7buwf7ka011l7c0srvjby04bq.png)
![\Rightarrow y+y Ae^(kt) = Ae^(kt)](https://img.qammunity.org/2021/formulas/mathematics/college/erqpe6dmxk2hfcgbln6veqrrzfw1btbsb5.png)
![\Rightarrow y(1+Ae^(kt) )= Ae^(kt)](https://img.qammunity.org/2021/formulas/mathematics/college/7tbhu676jjiu37st4k9snduhdqzlkk3pmm.png)
![\Rightarrow y= (Ae^(kt))/(1+Ae^(kt) )](https://img.qammunity.org/2021/formulas/mathematics/college/u10ay6fkjf5lj0aoworuexe78wkbbp8cmr.png)
Therefore ,
![y= (Ae^(kt))/(1+Ae^(kt) )](https://img.qammunity.org/2021/formulas/mathematics/college/h7h0xl0w8q3o10y8xiudic01hxg2w3an3f.png)